PENGUJIAN VALIDASI KONTEN KUESIONER GHSQ-V UNTUK GENERASI Z VERSI BAHASA SUKU KODI - Ahmad Guntur; Yohanis Dodok; Kurniawan Erman Wicaksono (STIKes Buleleng, 2022)
The purpose of the study was to test the validity of the content of the GHSQ-V in the regional language version of the Kodi tribe. This research was conducted by starting literature on The GHSQ-V. The study was conducted in January 2022 using the GHSQ-V instrument. The questionnaire was obtained in the English version and then switched to language using Indonesian language in accordance with who guidelines on translation. Then the questionnaire was translated into Kodi tribal language to 3 experts, namely the Chief of The Kodi Tribe, students of the original Kodi Tribe Indonesian Study Program and nurses who were the holders of mental health programs of The West Sumba District Kodi Health Center. all three experts on the kodi language version of the sample sample found the mean I-CVI, item-level content validity index rat-average = 0.87, then the average proportion rated relevant from the first expert = 0.90, the second expert = 1.00, and the third expert = 0.80.GHSQ-V into the Indonesian version becomes a general search-seeking behavior questionnaire in general and in the kodi tribal language. The questionnaire is declared valid through content validation calculations